To disclose or not to disclose? Caregivers experiences of disclosure of HIV status of children living with HIV in Accra, Ghana - Delight Abla Klutsey MPhil; Margaret Amankwah‐Poku PhD; Kwaku Oppong Asante PhD (Wiley, 2021)
Abstract Background Status disclosure remains a major challenge for most caregivers of children living with HIV/AIDS, and it remains suboptimal, resulting in reduced adherence and negative psychological and physical outcomes in these children. This study explored caregivers' experiences of disclosure of the HIV status of their affected children within the Greater Accra Region of Ghana. Methods Using the interpretive phenomenological qualitative approach, in‐depth interviews were conducted among 15 caregivers (aged 27-55 years) who were either the biological parents or guardians of children living with HIV (aged 6-15 years) from three main hospitals giving antiretroviral care in the Greater Accra Region. Interviews focused on the reasons for disclosure, the process of disclosure, and the aftermaths of disclosure. The interviews were recorded, transcribed, and subsequently analyzed thematically. Results Three main themes emerged from the analysis: "The Despair of HIV Diagnosis," "The Dilemma and Nuances of Disclosure," and "Aftermaths of Disclosure" Generally, the diagnosis of HIV in the children came as a shock to most caregivers which led to subsequent testing and diagnosis of caregivers. Two forms of disclosure were observed from the narratives: partial and full disclosure. Reasons for full disclosure were the child's curiosity, non‐adherence to antiretroviral therapy, and transition to high school. Non‐disclosure was as a result of stigma, the child been too young, and a lack of skill to disclose. Overall, caregivers reported that disclosure improved adherence and well‐being in their children; and helped reduce tension and anxiety among caregivers. Conclusions These findings suggest disclosure of HIV status to children living with HIV/AIDS has the potential to positively influence health outcomes in these children. However, caregivers need to be educated to initiate disclosure with the needed assistance from health care providers.